Vortex filament flows for curves in a 3-dimensional pseudo-Riemannian manifold - Yüzbai, Zühal Küçükarslan; Gürbüz, Nevin Ertug; Lee, Hyun Chul; Yoon, Dae Won (Birkhauser, 2024)
In this work, we focus on the evolution of the vortex filament flow ???t=???s?Dds???s for spacelike and timelike curves in a 3-dimensional pseudo-Riemannian manifold. We study the relations between a partial differential equation and the vortex filament flow for spacelike and timelike curves. As a result, we prove that the vortex filament flow of the spacelike curve in a 3-dimensional pseudo-Riemannian manifold with constant sectional curvature is equivalent to the heat equation, and the flow of the timelike curve is equivalent to the non-linear Schrödinger equation. Also, we give some examples to illustrate the vortex filament flow. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2023.
Keywords: Evolution equation; Heat equation; Non-linear Schrödinger equation; Primary 53C50; Pseudo-Riemannian manifold; Secondary 35Q55; Vortex filament flow